ANALISIS INPUT OUTPUT SEKTOR KEHUTANAN DI PROVINSI JAWA TENGAH TAHUN 2000 - 2008 - , Ridwan Pambudi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The role of forestry sector in the economy of Central Java province is quite large and strategic. Based on the data from the Central Statistics Agency (BPS), however, the contribution of forestry to Gross Domestic Product (GDP) over the past 10 years is relatively small. This study was conducted to determine the actual role of forestry in the economy of Central Java through the contribution to GDP, the linkages with other sectors, and the ability to encourage the economic growth. The input-output analysis was used in this study to show the ignored aspects such as multiplier effects and linkages among the sectors. The data was taken from The Input Output Table of Central Java in 2000, 2004 and 2008. The analyses conducted in this research involve contribution analysis, multiplier analysis, linkage analysis and key sectors analysis by using the Rasmussen / Hirschmanâs method. The result showed that the contribution of forestry sector to the economy output of Central Java fluctuates. The largest contribution was donated by the furniture industry and wood industry, while the smallest one was donated by pulp and paper industry and other forest products sector. The contribution of forestry sector is larger than the primary forest. The largest intermediate demand contribution came from wood sector and wood industry, while the smallest contribution came from the furniture industry and other forest products. The largest contribution to the final demand was contributed by the furniture industry, while the other forest products sectors and timber industries provide the greatest contribution to the gross value added. Furniture industry has the highest output multiplier index of among all sectors. Generally, the forestry industry has bigger income multiplier than the primary forest. This indicates that the forestry industry has a high ability to increase the output and double the income. Backward linkages of the forestry industry are quite high throughout the sector. Backward linkages value in forestry sector is higher than its forward linkage. Based on the key sector analysis, the timber industry was categorized into key sector, while the furniture industry and the pulp and paper industry were categorized into the backward linkage oriented sectors. Primary forest (wood sector and other forest products sector) was categorized into footloose sector.